Democratic Model for Village Economic Resource Management in Nglanggeran, Gunungkidul - Puthut Indroyono; Hempri Suyatna; Awan Santosa; Istianto Ari Wibowo; Rindu Sanubari Mashita Firdaus (Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This article seeks to describe the results of the research with the topic of developing a model of governance of natural resources at the level of the rural communities involving community participation, both in terms of production, distribution aspects, and aspects of the control of the factors of production. By taking the case of the village Nglanggeran, it sought to create a model of governance “alternative” in the failure of the model of “state” and “market” in protecting people’s socio-economic interests of the community from systemic poverty and the threat of sustainable ecological environment. The experience of developing governance of a natural democracy in this village is expected to illustrate the potential, problems and alternatives completion faced by communities in improving the welfare in a fair and equitable manner.